Rupiah’s Overshooting Phenomenon - Doni Briliant (Kusuma Negara Business School, 2020)
This research aims to find out whether Rupiah to US Dollar exchange rate experienced overshooting or not. In addition, this research examines the short-term partial effect between GDP (Gross Domestic Product), Inflation and Interest Rates on the Rupiah exchange rate. The data used in this research were quarterly secondary data on Rupiah/USD spot exchange rates, Constant GDP, Consumer Price Index (CPI), and Bank Indonesia Interest Rates in the 2007-2018 period. The analytical method used in this research is Autoregressive Distributed Lag (ARDL). The results showed that the Rupiah experienced overshooting, in addition to partial testing shows that in the short term, GDP has a negative effect on the Rupiah exchange rate, inflation has a positive effect on the Rupiah exchange rate, and interest rates have no negative effect toward the Rupiah exchange rate.